A Determinants Model for Shallot Productivity Based on Farmers' Socio-Economic Factors in Pota Village: Model Determinan Produktivitas Bawang Merah Berdasarkan Faktor Sosial Ekonomi Petani di Kelurahan Pota - Wensislaus Arman Ndau; Fatchur Rozci (Jurnal Ilmiah Sosio Agribis, 2026)
Shallots hold a strategic position in Indonesia's food and agribusiness systems. This commodity has the potential to boost farmers' incomes and improve the well-being of rural communities, particularly in areas with high onion consumption. Shallot productivity at the farmer level shows significant variation between regions, even within the same region. Farmers' socioeconomic factors are believed to influence these differences in productivity. This study aims to analyze the socioeconomic factors that influence shallot productivity among farmers. The study was conducted in Pota Village, Sambi Rampas District, as it is the center of shallot production in East Manggarai Regency. This research is included in the quantitative approach design. A sample of 35 shallot farmers was taken using total sampling. The data were analyzed using a multiple linear regression model. The results showed that socioeconomic factors simultaneously had a significant effect on shallot productivity. Partially, socioeconomic factors such as land area, education level, and farming experience significantly influence shallot productivity. Meanwhile, farmer age and number of dependents in the family do not. The coefficient of determination indicated that shallot productivity in Pota Village was dominated by socioeconomic factors, accounting for 64.1%.